International licensing and R&D subsidy - Cuihong Fan; Zhentang Zhang (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
R&D rivalry and optimal R&D policies are investigated in an asymmetric four-stage game that involves international licensing. It is found that a government's R&D policy crucially depends on its domestic firm's bargaining power over the licensing gain. When the firm's bargaining power is greater than one half, the government subsidizes its home firm's R&D investment, while imposes a tax if the firm's bargaining power is less than one half. Additionally, this result does not depend on the status of the firm (the licensor or the licensee). Finally, the effects of two different licensing contracts (fixedfee v.s. royalty per unit) on governments' optimal R&D policies are investigated. – – Der Beitrag beschäftigt sich mit Innovationswettbewerb und der Rolle von nationaler Politik im Falle von internationalen Lizenzierungspraktiken. In einem mehrstufigen Spiel werden die Anreizmechanismen untersucht. Es stellt sich heraus, daß die Verhandlungsstärke der nationalen Unternehmen im Lizenzierungsmarkt eine wichtige Rolle spielen. So erfolgt aus nationaler Sicht eine Subvention (Besteuerung) von F&EInvestitionen immer dann, wenn die Verhandlungsmacht groß (klein) ist. Darüber hinaus untersucht der Beitrag die Konsequenzen unterschiedlicher Lizenzierungspraktiken auf die optimale nationale F&E-Politik.
Keywords: L13; O34; 330; International Licensing; R&D Subsidy; R&D Investment